Visual Expression of Insight Through Nature - Janette Kiara Zerlinda Santosa; Ariesa Pandanwangi; Wawan Suryana (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2022)
Nature inspires many artists, and is explored through visual expression using various media and techniques. Various streams that visualize this include realism or naturalism. These visual expressions can represent and record nature. Visual expressions that are conveyed in an abstract form that can provide a natural atmosphere by bringing calm, comfort, have not been explored by many artists both from within and outside the country. This creation aims to find out how to convey a calm situation through art works to art appreciators. The benefit of this creation for the development of society is that it can create a